FROM ‘VICTIM’ TO ‘SURVIVOR’: DECONSTRUCTING THE PERVASIVE NOTION OF VICTIMHOOD IN DISCOURSES AROUND PROGRAMMES DEALING WITH GENDER-BASED VIOLENCE - Leburu, Goitseone (Social Work, 2023)
Social workers are among key professionals rendering empowerment services to people affected by gender-based violence in South Africa. These services are rendered within the developmental and empowerment approaches that were introduced in the post-apartheid era. Although the introduction of democracy brought a paradigm shift towards a developmental approach, social welfare and social work, there is paucity of research that investigates the utilisation of the concept of “victim” within the empowerment services rendered to people harmed by gender-based violence. The concept of “victim” has not been extensively researched theoretically and empirically. This article critically analyses the usage of the concept of “victim” in the empowerment social work services and posits a deconstruction of the pervasive notion of victimhood in discourses around programmes dealing with gender-based violence. It is hoped that this article will stimulate debates and research focused on the labels adopted in the empowerment services, as well as in developmental and social work in different societal contexts. Keywords: developmental approach, empowerment, social work, survivor, victim